Asupan magnesium, kalsium, purin, vitamin c, kafein dan kadar asam urat pada wanita menopause - Hana Atikah; Yulia Wahyuni; Anugrah Novianti (University of Darussalam Gontor, 2020)
Latar Belakang: Kadar asam urat cenderung meningkat pada wanita yang sudah mengalami menopause. Asupan tinggi purin dapat meningkatkan kadar asam urat. Sedangkan menjaga asupan vitamin C, kalsium dan magnesium dalam batas wajar berpotensi mengurangi kadar asam urat dalam darah. Tujuan: Menganalisis hubungan antara asupan magnesium, kalsium, vitamin C, purin dan kafein terhadap kadar asam urat wanita menopause.Metode: Desain penelitian ini adalah cross-sectional. Subjek adalah wanita menopuse rentan usia 51-92 tahun berjumlah 70 orang. Data asupan purin, vitamin C, kalsium, magnesium dan kafein diperolehmenggunakan formulir Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ) dan kadar asam urat dengan alat Easy touch GCU. Analisis bivariat dengan uji korelasi Pearson dan Spearman. Hasil: Rerata kadar asam urat 5,949 ± 1,79 mg/dl. Sebanyak 44,29% subjek memiliki asupan purin tinggi, sebanyak 64,3% subjek memiliki asupan vitamin C yang rendah. Terdapat hubungan antara asupan purin, vitamin C dan kalsium terhadap kadar asam urat subjek (p = 0,003 ; p = 0,011 ; p = 0,037 secara berurut). Tidak terdapat hubungan antara asupan magnesium dan kafein terhadap kadar asam urat subjek ( p = 0,545 ; p = 0,358 secara berurut). Kesimpulan: Terdapat hubungan yang signifikan antara asupan purin, kalsium dan vitamin C terhadap kadar asam urat pada subjek. Background: Uric acid levels tend to increase in women who have experienced menopause. High purine intake is thought to be one of the causes of increased uric acid levels. While maintaining the intake of vitamin C, calcium and magnesium and caffeine within the recommended limits have the potential to reduce uric acid levels in the blood. Objective: To determine the relationship between intake of purines, vitamin C, calcium, magnesium, and caffeine intake on uric acid levels in menopausal women in the Mampang sub-district health center. Method: Cross-sectional was the design of this study. The sample used was menopausal women vulnerable to age 51-92 years totaling 70 people in the Mampang District Health Center. Data on the intake of purines, vitamin C, calcium, magnesium, and caffeine were obtained by conducting interviews using semi-quantitative food frequency and uric acid levels using the Easy touch GCU tool. Bivariate analysis was performed using Pearson and Spearman correlation tests. Results: The average level of uric acid respondents 5.949 ± 1.79 mg/dl. As many as 44.29% of respondents had high purine intake and 64.3% of respondents had low vitamin C intake. There was a significant relationship between intake of purines, vitamin C and calcium on uric acid levels of menopausal women (p = 0.003; p = 0.011; p = 0.037 sequentially). But no association was found between magnesium and caffeine intake on uric acid levels in menopausal women (p = 0.545; p = 0.250 sequentially). Conclusion: There was a significant relationship between intake of calcium, purines, vitamin C and on uric acid levels in menopausal women in the Mampang sub-district health center. Suggestion: The consumption of respondent's vitamin C is low, therefore increasing the consumption of fruits and vegetables is sufficient in good menopausal women to prevent increased uric acid levels.